Chiral weak ferromagnets formed in one-dimensional organic–inorganic hybrid manganese chloride hydrates. Issue 44 (27th October 2022) - Taniguchi, Kouji; Huang, Po-Jung; Kimura, Shojiro; Miyasaka, Hitoshi
Abstract : Chiral weak ferromagnets were developed in one-dimensional organic–inorganic hybrid chain compounds comprising manganese chloride hydrate of deformed perovskite derivatives. Abstract : Chiral weak ferromagnets were developed in organic–inorganic hybrid systems of one-dimensional manganese(ii ) chloride hydrate with chiral organic cations of ( S )- and ( R )-β-methylphenethylammonium (= ( S )- and ( R )-MPA + ), [( S )/( R )-MPA]2 [MnCl4 (H2 O)]. The weak ferromagnetic phase found below 3.2 K could be attributed to a spin canting antiferromagnetic state induced by Dzyaloshinskii–Moriya interactions owing to spatial inversion symmetry breaking in chirality introduced systems. This is the first chiral weak ferromagnet found in a spin chain of deformed perovskite derivatives with a corner-sharing structure of transition metal halide hydrates.